Multilevel state policy on the basis of the open model of innovation process management; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Akerman E. N. Elena Nikolaevna; Kozlovskaya O. V. Oksana Vitalievna; Barysheva G. A. Galina Anzelmovna; Burets Yu. Yuliya (2016, 2016)
Title screen